Budgets and Financial Management in Higher Education - Barr, Margaret J.; McClellan, George S. (The Jossey-Bass higher and adult education series, 2018)
This book can help new administrators (department chairs, directors, deans) understand and become more proficient in their financial management role within the institution. Practitioners will be able to put the book's guidance to immediate use in their work. It is also filled with examples from across all types of institutions, so that it makes an ideal text for a courses in graduate programs in higher education leadership and administration. This book provides an understanding of the basics of budgeting and fiscal management in higher education, defines the elements of a budget, the budget cycle, and the steps for creating a budget, and suggests ways of avoiding common pitfalls and problems of managing budgets. Readers will be introduced to Bowen's theory of resources and expenses as an important way to understand budgetary decision making in colleges and universities. Special attention is paid to the use of restricted funds, the budget implications of faculty appointments, and the challenges caused by personnel policies for staff. In addition, greater attention is given to development and implementation of repair and replacement programs in auxiliary enterprises. The challenges that arise when budget problems are postponed are also discussed. The volume contains a number of suggestions for practitioners with new budgeting and fiscal responsibilities.